2015
DOI: 10.1136/bmjopen-2015-007976
|View full text |Cite
|
Sign up to set email alerts
|

Severe sepsis in women with group BStreptococcusin pregnancy: an exploratory UK national case–control study

Abstract: ObjectiveTo estimate the incidence of severe maternal sepsis due to group B Streptococcus (GBS) in the UK, and to investigate the associated outcomes for mother and infant.DesignNational case–control study.SettingAll UK consultant-led maternity units.Participants30 women with confirmed or suspected severe GBS sepsis, and 757 control women.Main outcome measuresDisease incidence, additional maternal morbidity, critical care admission, length of stay, infant infection, mortality.ResultsThe incidences of confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 18 publications
(24 reference statements)
3
22
0
1
Order By: Relevance
“…We intended to estimate incidence rates per 1000 pregnancies; however only 1 study reported these data [ 26 ]. Four more used maternities as the denominator [ 12 , 14 , 40 , 42 ], which we used for the meta-analysis. The number of maternities will be lower than the number of pregnancies, as pregnancies include miscarriages and induced abortions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We intended to estimate incidence rates per 1000 pregnancies; however only 1 study reported these data [ 26 ]. Four more used maternities as the denominator [ 12 , 14 , 40 , 42 ], which we used for the meta-analysis. The number of maternities will be lower than the number of pregnancies, as pregnancies include miscarriages and induced abortions.…”
Section: Resultsmentioning
confidence: 99%
“…The number of maternities will be lower than the number of pregnancies, as pregnancies include miscarriages and induced abortions. The studies included in the meta-analysis of the incidence of maternal GBS disease were all published since 2013 (and included 1 set of unpublished data) and were conducted in the United States [ 12 ], France [ 14 ], Ireland [ 26 ], and the United Kingdom [ 40 , 42 ] ( Figure 3 ). Four were conducted retrospectively and 1 prospectively, and they were all large studies covering tens or hundreds of thousands of women.…”
Section: Resultsmentioning
confidence: 99%
“…A combination of both resulted in a maximum cost-effective price of £100. To date, no maternal deaths caused by GBS have been reported in the UK [35,58].…”
Section: Scenario Analysismentioning
confidence: 99%
“…GBS is also known to cause severe invasive infections in adults. GBS infection has been reported in 12 per 100,000 pregnancies typically as endometritis, urinary tract infections, and occasionally, maternal bacteremia [ 17 , 19 ]. GBS can also cause significant morbidity in non-pregnant adults; while relatively rare in younger individuals, invasive GBS infection incidence is 24 per 1,000,000 in those over age 65 [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…GBS infection has been reported in 12 per 100,000 pregnancies typically as endometritis, urinary tract infections, and occasionally, maternal bacteremia [ 17 , 19 ]. GBS can also cause significant morbidity in non-pregnant adults; while relatively rare in younger individuals, invasive GBS infection incidence is 24 per 1,000,000 in those over age 65 [ 19 ]. In non-pregnant adults, GBS infection generally presents as soft tissue infection (22%), osteomyelitis/septic arthritis (18%), pneumonia (11%), or bacteremia without identifiable focus (48%) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%